2021
DOI: 10.1088/1755-1315/722/1/012005
|View full text |Cite
|
Sign up to set email alerts
|

Visible light assisted photocatalytic degradation of Rhodamine B dye on CdSe-ZnO nanocomposite: Characterization and kinetic studies

Abstract: The paper involves the heterogeneous photocatalytic degradation of Rhodamine B dye (RhB) employing ZnO and ZnO/CdSe nanocomposites as photocatalysts which was synthesized via chemical bath deposition (CBD) method. Nanocomposite CdSe-ZnO powders have been synthesized by varying CdSe/ZnO molar ratios. The structural, optical, morphological, and topological characteristics of as synthesized materials were investigated using the appropriate characterization instrument such as X-ray diffractometer (XRD), diffuse re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…Several previous studies have reported on several reactions that take place in a photocatalytic process and involve H 2 O 2 , •OH and O 2 • − . Hence, the relevant reactions on the Cs 2 HgI 4 surface making the colorant degeneration can be described below [35] , [36] , [37] , [38] : Cs 2 HgI 4 + hν (Visible) → Cs 2 HgI 4 (e − + h + ) Cs 2 HgI 4 (e − ) + O 2 → Cs 2 HgI 4 + O 2 • − Cs 2 HgI 4 (h + ) + H 2 O → Cs 2 HgI 4 + H + + OH• Cs 2 HgI 4 (h + ) + OH − → Cs 2 HgI 4 + OH• H 2 O 2 →hν2•OH H 2 O (ads) + h + → •OH + H + OH − (ads) + h + → HO• O 2 + e − → O 2 • − O 2(ads) + e − + H + → HO 2 • HO 2 • + HO 2 • → H 2 O 2 + O 2 O 2 • − + HO 2 • → HO 2 − + O 2 HO 2 − + H + → H 2 O 2 H 2 O 2(ads) + e − → •OH + OH − H 2 O 2 + O 2 • − → •OH + OH − + O 2 H 2 O 2(ads) + 2 h + → O 2 + 2H + H 2 O 2(ads) + 2H + + 2e − → 2H 2 O H 2 O 2(ads) + h + → HO 2 • + H + O 2(ads...…”
Section: Resultsmentioning
confidence: 99%
“…Several previous studies have reported on several reactions that take place in a photocatalytic process and involve H 2 O 2 , •OH and O 2 • − . Hence, the relevant reactions on the Cs 2 HgI 4 surface making the colorant degeneration can be described below [35] , [36] , [37] , [38] : Cs 2 HgI 4 + hν (Visible) → Cs 2 HgI 4 (e − + h + ) Cs 2 HgI 4 (e − ) + O 2 → Cs 2 HgI 4 + O 2 • − Cs 2 HgI 4 (h + ) + H 2 O → Cs 2 HgI 4 + H + + OH• Cs 2 HgI 4 (h + ) + OH − → Cs 2 HgI 4 + OH• H 2 O 2 →hν2•OH H 2 O (ads) + h + → •OH + H + OH − (ads) + h + → HO• O 2 + e − → O 2 • − O 2(ads) + e − + H + → HO 2 • HO 2 • + HO 2 • → H 2 O 2 + O 2 O 2 • − + HO 2 • → HO 2 − + O 2 HO 2 − + H + → H 2 O 2 H 2 O 2(ads) + e − → •OH + OH − H 2 O 2 + O 2 • − → •OH + OH − + O 2 H 2 O 2(ads) + 2 h + → O 2 + 2H + H 2 O 2(ads) + 2H + + 2e − → 2H 2 O H 2 O 2(ads) + h + → HO 2 • + H + O 2(ads...…”
Section: Resultsmentioning
confidence: 99%
“…As was shown by the authors [38], a decrease in particle size leads to an increase in the efficiency of decomposition, which also coincides with the results of this work, according to which the formation of finer grains in NiCdSe and CoCdSe also affects decomposition efficiency. The highly efficient influence of composite structure formation achieved by the modification of CdSe materials by adding ZnO to them on the subsequent formation of nanocomposites was demonstrated in [40]. According to the results of [40], the formation of a nanocomposite of the ZnO/CdSe type leads to the formation of stable photocatalysts capable of operating for more than 15 consecutive cycles, which also confirms the assumption made in this study about the influence of nickel and cobalt on increasing the stability of long-term photocatalyst operations.…”
Section: Type Of Organic Dye Rhodamine Bmentioning
confidence: 99%
“…The highly efficient influence of composite structure formation achieved by the modification of CdSe materials by adding ZnO to them on the subsequent formation of nanocomposites was demonstrated in [40]. According to the results of [40], the formation of a nanocomposite of the ZnO/CdSe type leads to the formation of stable photocatalysts capable of operating for more than 15 consecutive cycles, which also confirms the assumption made in this study about the influence of nickel and cobalt on increasing the stability of long-term photocatalyst operations. The results obtained in this work on the efficiency of the photocatalytic decomposition of organic dyes are in good agreement with the results of work [41], which examined three types of photocatalysts based on CdSe modified with graphene and TiO 2 .…”
Section: Type Of Organic Dye Rhodamine Bmentioning
confidence: 99%
“…And the proposed geometry is octahedral with deformed deformation, and the deformation type is compressed (Z-in) or dragged (Z-out). The most common possibility is (Z-out) and its sp3d2 hybridization (Alshamsi et al 2021).…”
Section: Electronic Spectra Studies Electronic Spectra Of Free Ligand...mentioning
confidence: 99%